Global marketing and advertising : understanding cultural paradoxes - De Mooij, Marieke K., 1943- (Los Angeles : SAGE Publications, 2014)
Packed with cultural, company, and country examples that help explain the paradoxes international marketers are likely to encounter, Global Marketing and Advertising, Third Edition, offers a mix of theory and practical applications as it covers globalization, global branding strategies, classification models of culture, and the consequences of culture for all aspects of marketing communications. In this Third Edition, author Marieke de Mooij includes new topics and updated information and findings from recent studies and helps readers apply global marketing concepts to the management of global branding and marketing communications. New and Continuing Features Includes new topics, including global public relations, culture and the media, and culture and the Internet, along with more extensive coverage of consumer behavior Helps companies define cross cultural segments to better target consumers across cultures Shows how culture affects strategic issues, such as the company's mission statement, brand positioning strategy, and marketing communications strategy Includes both recent and classic advertising examples from various parts of the world Demonstrates the centrality of value paradoxes to cross cultural marketing communications Uses the Hofstede model to help readers see how their understanding of cultural relationships in one country/region can be extended to other countries/regions.
Includes bibliographical references and index.
Keywords: Advertising -- Cross-cultural studies; Consumer behavior -- Cross-cultural studies; Global marketing; Go international; International office; Reclame; Target marketing -- Cross-cultural studies